Contextual Nonlinear Typological Analysis as a Tool for the Formation and Implementation of Regional Economic Policy - V. A. Kurzenev; V. T. Perekrest (Управленческое консультирование)
The article outlines the main theoretical and methodological positions on the formation and implementation of regional economic policy in relation to technological innovations. It is based on contextual typological analysis using economic and mathematical modeling, where the key role is played by the hybrid principal component method and scaling technology. Official statistics data are used as information and analytical support. The concept of network rating for spatial economic systems is introduced and the analysis of regional systems is carried out. A convenient visualization system for analyzing and making management decisions based on statistical information is proposed.